Doctrinal Aspects of the US, NATO and EU Policies in Military Space - A. I. Nikitin; M. V. Klinova (Сравнительная политика, 2024)
Exploration of an outer-space initially and currently is closely related to militarization. All spacecraft, in one way or another, have a dual purpose and can be used for both peaceful and military purposes – from the use of launchers for orbital and suborbital flights to telecommunication systems. In the doctrinal documents of the USA, NATO and the European Union space is considered, among other functions, as a source of “space threats” and as an environment for potential military operations. Military space forces and Commands are structurally separated into a special category within the Armed Forces of Western countries. Comparative analysis of NATO and EU space strategies shows significant differences. NATO places an emphasis on the use of already existing space resources of its member states to implement its traditional goals and objectives, without concentrating on the formation of collective structures advancing space technologies. EU, in contrast, actively integrates technological inputs of its member states with powerful economic potential, initiates and develops collective inter-state projects and structures for space exploration. EU in recent times pays special attention to attempts to ensure European strategic autonomy from the USA and third countries in the space sector. The increasingly intensive entry of private enterprises into the outer space sector has been a characteristic feature at the beginning of the 21st century, their role is expanding, and cooperation of businesses with the state is strengthening on a commercial basis in the form of public-private partnerships.